Análisis del uso de Instagram como herramienta de información del GAD Yantzaza para la población de 18 a 40 años, en el período mayo-agosto 2022. - Britney, Enríquez Santín (2022)
The present research work has as its theme "Analysis of the use of Instagram as an information tool of the GAD Yantzaza for the population between 18 and 40 years of age, in the period May - August 2022". Instagram as a social network in public institutions plays an important role in organizational communication, since thanks to this social network it has been possible to directly reach virtual communities. However, the lack of application of communication strategies has become an obstruction to raise the levels of notoriety and image of an institution; for which the present investigation has as objective, to analyze the institutional informative contents and the use of the social network Instagram in the Decentralized Autonomous Government of the Yantzaza canton, in such a way that the contents and the impact that these generate through each publication, as well as examine the informative organization of the content that is posted through Instagram, in order to propose an alternative to renew the communicational content. The research was complemented with a mixed methodology, where research techniques and tools were used, such as: interviews, surveys, observation and bibliographic review. Among the results, it was found that they have little interactivity and reach of the users, due to the lack of a communication plan and manual for the use of Instagram that allow improving the contents that are published on the official page of the Gad de Yantzaza, considering important the use communication strategies linked to technology. Keywords: Instagram, Social networks, Communication, Technology, Tools Informations.